Hubungan Persentase Kesesuaian Asupan Makronutrien dengan Status Gizi pada Remaja SMA di Surakarta - Nafisa Annida Lil Mau'idhoh; Dyah Intan Puspitasari; Firmansyah Firmansyah (Yayasan Literasi Sains Indonesia, 2026)
Adolescent nutrition problems are still a concern due to the imbalance between nutrient intake and needs during a period of rapid growth. This study aims to analyze the relationship between the percentage of conformity of macronutrient intake with nutritional status in high school adolescents in Surakarta based on energy distribution. This study is an observational study with a cross-sectional design involving 221 respondents selected through a proportional random sampling technique. Macronutrient intake data was collected using 3x24-hour food recall and analyzed with NutriSurvey 2007, while nutritional status was determined based on BMI by age (BMI/U) using WHO AnthroPlus. Data analysis was carried out using the Chi-Square test with a significance level of p<0.05. The results showed that most of the respondents had normal nutritional status (72.9%). The percentage of appropriate protein intake was significantly associated with nutritional status (p=0.037), while the percentage of appropriate fat (p=0.111) and carbohydrate (p=0.911) intakes did not show a significant relationship. This demonstrates the importance of appropriate amino acid intake for somatic growth and indicates that adolescents have metabolic flexibility in regulating energy sources. Future researchers are advised to expand the scope of variables to include physical activity, snacking behavior, and social factors.